2020
DOI: 10.1039/d0cp01127d
|View full text |Cite
|
Sign up to set email alerts
|

Excited-state proton transfer in protonated adrenaline revealed by cryogenic UV photodissociation spectroscopy

Abstract: Excited state proton transfer is the main non radiative deactivation process in protonated adrenaline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…S1). Such photo-specific bond cleavage has also been observed in related systems, such as protonated aromatic amino acids 20 and catecholamines 10,21 and assigned to an excited state proton transfer reaction from the ammonium to the aromatic ring. 9 FIG.…”
mentioning
confidence: 63%
See 2 more Smart Citations
“…S1). Such photo-specific bond cleavage has also been observed in related systems, such as protonated aromatic amino acids 20 and catecholamines 10,21 and assigned to an excited state proton transfer reaction from the ammonium to the aromatic ring. 9 FIG.…”
mentioning
confidence: 63%
“…Recently, excited state dynamics of protonated adrenaline, a closely related catecholamine, has been reported. 10 It was found that the excited state proton transfer from the amine chain to the aromatic ring and H atom loss from the ammonium group compete with a branching ratio that depends on the excess energy. The energy barrier for both processes is relatively large, about 0.3 eV and 0.8 eV respectively, so the excited state dynamics is not ultrafast with lifetime in the nanosecond range.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Other groups have deployed femtosecond or picosecond pump-probe laser configurations combined with photodissociation mass-spectrometry to interrogate excited-state lifetimes of ions in tandem time-of-flight mass spectrometers, [133][134][135] triple-quadrupole mass spectrometers, 136 ion storage rings, 137,138 custom built ion traps at room temperature, [139][140][141] custom built ion traps that are cryogenically cooled, 81,85,132,142 and commercial ion traps. 87,[143][144][145][146] There are also setups using electronic delays for pump-probe photodissociation on the nanosecond to millisecond timescale.…”
Section: Pump-probe Photodissociationmentioning
confidence: 99%
“…The exothermic ESPT reaction has already been evaluated in similar systems and ranges from 0.2 eV for protonated tryptophan 27 to 0.5 eV for protonated tyrosine and phenylalanine 6 up to 0.9 eV for protonated adrenaline. 28 In any cases, the HOMO and LUMO molecular orbitals characterizing the ESPT structure are localized on the aromatic ring. However, in the ESPT structure of hydrated dopamine, after geometry optimization, the amino group becomes planar, revealing a change from sp 3 hybridization of the nitrogen atom toward sp 2 .…”
Section: Excited State Dynamics In Dah + (H 2 O) Nmentioning
confidence: 99%